Association between Lp(a) and small dense LDL in menopausal women without metabolic syndrome. Issue 3 (4th May 2019) - Gentile, Marco; Iannuzzo, Gabriella; Mattiello, Amalia; Marotta, Gennaro; Rubba, Fabiana; Iannuzzi, Arcangelo; Panico, Salvatore; Rubba, Paolo
Abstract: Background: Lipoprotein (a) (Lp [a]) is associated with premature atherosclerosis in menopausal women without metabolic syndrome (MS). MS is the main confounder in the relationship between Lp(a) and atherosclerosis in menopausal women. We have evaluated the relationship between Lp(a) and small dense-low density lipoprotein (sd-LDL) in 228 menopausal women participating to Progetto Atena. Methods: Lp(a) was measured and LDL particle separation was performed: mean LDL diameter and LDL score (% of sd-LDL) particles calculated. Results: Women without MS and elevated Lp(a) have increased number of sd-LDL ( p < .05) and higher LDL score compared with those below the median of the studied population ( p < .05). The association between Lp(a) and sd-LDL was evaluated taking into account different adjustment models. Women with elevated levels of Lp(a) show the following OR of having a small LDL diameter (in the lowest quartile): 1.02, p = .003; adjusted for age; 1.02, p = .002; adjusted for age, and triglycerides, or a high LDL score (in the highest quartile): 1.02, p = .006; adjusted for age; 1.02, p = .002; adjusted for age and triglycerides. Conclusions: In this group of menopausal women without MS, the independent association of Lp(a) with sd-LDL might explain at least in part the association of Lp(a) with premature atherosclerosis.